2005
DOI: 10.1016/j.jfms.2004.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Basal plasma insulin and homeostasis model assessment (HOMA) are indicators of insulin sensitivity in cats

Abstract: The objective of this study was to compare simpler indices of insulin sensitivity with the minimal model-derived insulin sensitivity index to identify a simple and reliable alternative method for assessing insulin sensitivity in cats. In addition, we aimed to determine whether this simpler measure or measures showed consistency of association across differing body weights and glucose tolerance levels. Data from glucose tolerance and insulin sensitivity tests performed in 32 cats with varying body weights (unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 33 publications
4
69
0
Order By: Relevance
“…Other researchers observed that insulin resistant obese dogs keep their glucose concentrations inside reference range [14]. The lower measurements of glucose observed in the present experiment in obese dogs were expected due to the higher stimulus of insulin in obese than in control animals, since serum basal insulin levels were higher in insulin-resistant dogs than in other groups, which agrees with data reported in dogs [15] and other species [10,16,17]. It is difficult to access insulin sensitivity in clientowned animals, as the ones that composed the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other researchers observed that insulin resistant obese dogs keep their glucose concentrations inside reference range [14]. The lower measurements of glucose observed in the present experiment in obese dogs were expected due to the higher stimulus of insulin in obese than in control animals, since serum basal insulin levels were higher in insulin-resistant dogs than in other groups, which agrees with data reported in dogs [15] and other species [10,16,17]. It is difficult to access insulin sensitivity in clientowned animals, as the ones that composed the present study.…”
Section: Discussionsupporting
confidence: 91%
“…It is difficult to access insulin sensitivity in clientowned animals, as the ones that composed the present study. High levels of fasting insulin and I/G ratio have been used as indirect measures of this metabolic unbalance [1,16,18,19]. Expectedly higher values of I/G ratio were found in insulin-resistant dogs, since this index was used to group the animals.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance was assessed using the homeostasis model assessment (HOMA) (Appleton et al 2005), which was calculated from fasting plasma insulin and fasting plasma glucose concentrations. A higher HOMA index indicates a higher degree of insulin resistance (Pratchayasakul et al 2011).…”
Section: Metabolic Parameters Insulin Resistance and Testosterone Lmentioning
confidence: 99%
“…Plasma insulin and GLP-1(7-36 amide) levels were determined via the Sandwich ELISA kit (LINCO Research, St Charles, MO, USA). Peripheral insulin resistance was assessed via the homeostasis model assessment (HOMA) as described in the previous studies (Haffner et al 1997, Appleton et al 2005. Plasma malondialdehyde (MDA) was determined using a HPLC-based assay (Grotto et al 2007).…”
Section: Plasma Analysismentioning
confidence: 99%